2014
DOI: 10.1039/c3ja50344e
|View full text |Cite
|
Sign up to set email alerts
|

Micro-sublimation separation of boron in rock samples for isotopic measurement by MC-ICPMS

Abstract: The technique of micro-sublimation for boron (B) separation in silicates has been evaluated carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The micro‐sublimation procedure was also found useful to separate boron from organic rich media, in contrast to other methods like the use of activated carbon, H 2 O 2 , organic matter specific resin or UV irradiation (Lemarchand et al, ). Recently, this micro‐sublimation was used (Wang et al, ; Liu et al, ; Pi et al, ) for rock samples, marine carbonate, sea water, and Porites coral samples with an aim to avoid introduction of organic residue to the purified sample through the ion‐exchange procedure. The quantitative recovery of boron from sea water and coral sample (Liu et al, ) was confirmed by the standard addition method (Foster et al, ).…”
Section: Analytical Methodology For Extraction and Purification Of Boronmentioning
confidence: 99%
See 1 more Smart Citation
“…The micro‐sublimation procedure was also found useful to separate boron from organic rich media, in contrast to other methods like the use of activated carbon, H 2 O 2 , organic matter specific resin or UV irradiation (Lemarchand et al, ). Recently, this micro‐sublimation was used (Wang et al, ; Liu et al, ; Pi et al, ) for rock samples, marine carbonate, sea water, and Porites coral samples with an aim to avoid introduction of organic residue to the purified sample through the ion‐exchange procedure. The quantitative recovery of boron from sea water and coral sample (Liu et al, ) was confirmed by the standard addition method (Foster et al, ).…”
Section: Analytical Methodology For Extraction and Purification Of Boronmentioning
confidence: 99%
“…The procedure involved the addition of a known amount of SRM 951a standard to a sample before micro‐sublimation and to another set of the same sample after sublimation, followed by the measurement of 11 B/ 10 B isotopic ratios in the two mixtures to calculate the boron concentration. For the natural rock samples, doping with NaCl was necessary, prior to micro‐sublimation, to recover boron from the digested silicates of the rock samples (Pi et al, ). The procedure is based on the fact that boron sublimates at a relatively low temperature (about 70°C) to leave the organic and alkaline matrices in solution or solid form.…”
Section: Analytical Methodology For Extraction and Purification Of Boronmentioning
confidence: 99%
“…GeoReM data for 2016); for the 3d transition elements we prefer to use the high-mass resolution, magnetic sector data of Townsend (2000) rather than lower resolution quadrupole MS data which might be vulnerable to polyatomic interferences. The USGS standard nepheline syenite STM-1 has been studied less thoroughly than other international rock standards and our adopted values were based on the compilations of Gladney & Roelandts (1988) and Govindaraju (1994) supplemented by later published ICP-MS (Korotev, 1996;Dai-Kin et al, 1998;Gouveia & Prudêncio, 2000;Bédard & Barnes, 2002;Alnour et al, 2015) and INAA data (Dai-Kin et al, 1998;D'Orazio, 1998;Panteeva et al, 2003;Smirnova et al, 2003;Pi et al, 2014); the REE data provide the most reliable analyses. Quartz syenite CAAS-1 has been little studied since its original issue and our adopted data are mainly those of Sine et al (1969) with a few later values: Sc, Co, Y, Yb, V (Hofmeyr, 1972); V (Fuge, 1973); Co, Cr, Cu, Ni, Sr, Zn (Brooks et al, 1985).…”
Section: Recommended Values For Standard Rocksmentioning
confidence: 99%
“…Several new methods for the separation and purification of boron prior to isotopic measurements have been proposed. In a protocol 362 based on sublimation of B, the silicate samples were first digested with HF and mannitol at 80 °C for 3 days. Doping the rock digests with a concentrated solution of NaCl before micro-sublimation in PFA vials appeared to suppress the evaporation of major elements and improve the B recovery.…”
Section: Sample Separation and Preconcentrationmentioning
confidence: 99%
“…A new method 379 for determining Ca isotope ratios by MC-ICP-MS with sufficient precision to explore genetic links between Earth and meteorites is included inTable 5.Accurate measurements of boron concentrations and isotope ratios by ICP-MSdepend on minimising losses and isotope fractionation during sample digestion and any subsequent manipulation of the samples. Mannitol is often added to an acid digest362, 377 to complex B but this does not always completely suppress B volatilisation. In an alternative strategy396 for determining B concentrations by ID quadrupole ICP-MS, rock powders were spiked with 10 B-enriched NIST SRM 952 (enriched boric acid) before dissolution in a slight excess of HF on a hot plate at 65-70 °C for up to 72 h. After centrifugation, the supernatant in ca.…”
mentioning
confidence: 99%